Aquatic resistance training: Acute and chronic effects. - Borreani, S.; Colado, J.; Calatayud, J.; Pablos, C.; Moya-Najera, D.; Travis Triplett, N. (Strength and Conditioning Journal, 2014)
The water environment has advantageous physical properties for exercise, and it is an alternative and complementary tool to perform resistance training (rt). Research in water-based exercise has been focused on aerobic exercise, and little is known about the effects of rt in water. This narrative review provides a compilation of the studies regarding acute and chronic effects of rt in water and initial guidelines based on the evidence. For a video abstract of this article, see video, supplemental digital content 1 http://links.lww.com/scj/a136.